Pharmacokinetics of flucloxacillin during prolonged intermittent renal replacement therapy in a 76-year-old man. (17th November 2019) - Fox, Emma; Cheng, Vesa; Rawlins, Matthew; Dyer, John; De Keulenaer, Bart; Page, Michael M.; Hoad, Kirsten; Roberts, Jason A.
Abstract : Prolonged intermittent renal replacement therapy (PIRRT) use has been increasing in critically ill patients with kidney dysfunction. PIRRT can affect the pharmacokinetics of many drugs, although no data is available to guide flucloxacillin dosing in this clinical scenario. Herein, we describe the pharmacokinetics of flucloxacillin, given at 1 g every 4 h during PIRRT, in a 76-year-old, critically ill patient with a methicillin-susceptible Staphylococcus aureus (MSSA) prosthetic joint infection complicated by bacteraemia. Blood samples were taken over 2 days including during a 9-h PIRRT session. A two-compartment model was developed to describe differences in clearance of flucloxacillin during PIRRT and off-PIRRT (9.45 vs. 6.89 L/h). A flucloxacillin dose of 1 g every 4 h during PIRRT therapy appeared to attain adequate exposures for MSSA sepsis in this patient, however higher doses may be required for infection sites with poor drug penetration.